Firm-level determinants of earnings in the formal sector of the South African labour market - Haroon Bhorat; Morne Oosthuizen; Kezia Lilenstein; François Steenkamp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Labour market analysis in the South African context provides a relatively robust understanding of the individual characteristics that influence wage differentials across workers (i.e. supply-side characteristics), but provides relatively little insight into the firm-level characteristics influencing these differentials (i.e. demand-side characteristics). This is largely due to the relative paucity of firm-level data in South Africa. Therefore, the availability of micro firm-level data derived from anonymous corporate and individual tax data, presents an opportunity to explore this relatively uncharted and important territory in the South Africa labour market. Therefore, this paper examines the firm-level (demand-side) characteristics that explain wage differentials across formal private sector workers in South Africa. Using the FEiLSDVj method, we measure the relative contribution of firm (demand-side) and individual (supply-side) characteristics in explaining wage formulation in the South African formal sector labour market, which advances the existing literature by including a developing country case. Consistent with results for the French and Austrian labour markets, approximately 61 per cent of wage variance is due to individual effects, while at least 13 per cent is due to firm-level effects. Overall, our results suggest that firms that are profitable, older, more capital-intensive, more productive, and involved in international trade pay higher wages, on average. Interestingly, and contrary to the literature, our results indicate a negative relationship between firm size and wages.
Keywords: D24; J31; 330; Administrative data; tax; firm level; wages